Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1186/1471-2407-6-152
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal exposures and the risk of intracranial meningioma in women: a population-based case-control study

Abstract: Background: The role of exogenous hormone exposures in the development of meningioma is unclear, but these exposures have been proposed as one hypothesis to explain the over-abundance of such tumors in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(158 citation statements)
references
References 30 publications
11
128
0
5
Order By: Relevance
“…In addition, as in this study, previous studies have found no association between oral contraceptive use and meningioma or glioma risk (Jhawar et al, 2003;Custer et al, 2006;Wigertz et al, 2006).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, as in this study, previous studies have found no association between oral contraceptive use and meningioma or glioma risk (Jhawar et al, 2003;Custer et al, 2006;Wigertz et al, 2006).…”
Section: Discussionsupporting
confidence: 65%
“…Because little is known of the etiology of brain tumors and current knowledge of how reproductive factors influence the risk is conflicting (12,13,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), we conducted an international population-based case-control study to investigate how reproductive history affects the risk of glioma and meningioma. Brain tumor growth and especially the growth of meningiomas has been reported to be related to pregnancy (28); therefore, we decided to investigate if the relations between pregnancy related factors and brain tumor risk differed between young (fertile ages) and older women.…”
Section: Introductionmentioning
confidence: 99%
“…Issues that might be examined include the criteria for inclusion in analyses, the definitions of exposures or outcomes,79 which confounding variables merit adjustment, the handling of missing data,80, 81 possible selection bias or bias from inaccurate or inconsistent measurement of exposure, disease and other variables, and specific analysis choices, such as the treatment of quantitative variables (see item 11). Sophisticated methods are used increasingly to simultaneously model the influence of several biases or assumptions82, 83, 84 …”
Section: (E) Describe Any Analyses Used To Assess the Robustness Ofmentioning
confidence: 99%